2021
DOI: 10.1111/jnc.15509
|View full text |Cite
|
Sign up to set email alerts
|

From psychiatry to neurology: Psychedelics as prospective therapeutics for neurodegenerative disorders

Abstract: The studies of psychedelics, especially psychedelic tryptamines like psilocybin, are rapidly gaining interest in neuroscience research. Much of this interest stems from recent clinical studies demonstrating that they have a unique ability to improve the debilitating symptoms of major depressive disorder (MDD) long‐term after only a single treatment. Indeed, the Food and Drug Administration (FDA) has recently designated two Phase III clinical trials studying the ability of psilocybin to treat forms of MDD with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 248 publications
0
24
0
5
Order By: Relevance
“…5-HT 2A agonists, such as psilocybin, have drawn interest for their anxiolytic and antidepressant effects. There is increasing evidence that 5-HT 2A receptor agonists modulate learning and memory function by improving neuroplasticity, functional neuronal connectivity, and activating anti-inflammatory pathways ( de Vos et al, 2021 ; Garcia-Romeu et al, 2021 ; Kozlowska et al, 2021 ). It was also demonstrated that the neocortical 5-HT 2A receptor binding is decreased in patients with AD ( Hasselbalch et al, 2008 ), which is correlated to cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…5-HT 2A agonists, such as psilocybin, have drawn interest for their anxiolytic and antidepressant effects. There is increasing evidence that 5-HT 2A receptor agonists modulate learning and memory function by improving neuroplasticity, functional neuronal connectivity, and activating anti-inflammatory pathways ( de Vos et al, 2021 ; Garcia-Romeu et al, 2021 ; Kozlowska et al, 2021 ). It was also demonstrated that the neocortical 5-HT 2A receptor binding is decreased in patients with AD ( Hasselbalch et al, 2008 ), which is correlated to cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Dendritic change can alter the enhancement and suppression of membrane excitability, which may create opposing actions on dendritic excitability that promote plasticity (Savalia et al, 2021). Although the cellular mechanisms leading to therapeutic efficacy are not yet understood, serotonergic psychedelics stimulation of neural and glial cells may reduce inflammation and reduce oxidative stress and act as disease-modifying therapeutics in neurodegenerative disorders (Kozlowska et al, 2021). Biomarkers of plasticity are also demonstrated in clinical research, showing elevation of blood plasma brain-derived neurotrophic factor (BDNF) after administration of 200 mg of LSD compared with placebo (Holze et al, 2021).…”
Section: R Methodological Considerationsmentioning
confidence: 99%
“…LSD is a powerful partial agonist at cortical and subcortical 5-HT2A receptors of GABAergic interneurons (Marek and Aghajanian, 1996;Inserra et al, 2021a,b). Psychedelics also stimulate 5-HT1A receptors (Strassman, 1996;Carter et al, 2005;Pokorny et al, 2016) and 5-HT2B receptors (Kozlowska et al, 2021). Stimulation of the 5-HT1A receptor and GABA interneurons by LSD both inhibit and disinhibit prefrontal pyramidal cell activity (Llad o-Pelfort et al, 2012;Celada, et al, 2013a;Llad o-Pelfort et al, 2018) and show downstream effects on dopaminergic (Vollenweider et al 1999) and glutamatergic systems (Mason et al, 2020;Vollenweider and Preller, 2020).…”
Section: J Pharmacology Plasticity and Contextmentioning
confidence: 99%
“…From molecular mechanisms in cultured cells (Agbaegbu Iweka et al, 2021; Bendahmane et al, 2020), neurochemical mechanisms in intact organisms (Abreu et al, 2021; Becker et al, 2021), new imaging and quantitative methodologies providing insight into neurochemical changes (Abdalla et al, 2020; Arber et al, 2021; Blank & Hopf, 2021; Dienel, 2021) and critical biomarkers in disease (Altmayer et al, 2021; Chakraborty & Basu, 2021; Chatterjee et al, 2021; Eden et al, 2021; Geula et al, 2021; Ginsberg et al, 2021; Glezer et al, 2021), the scope of the Journal of Neurochemistry has broadened to respond to the demands of our scientific community. Neurochemical mechanisms of disease are a popular topic covering neuropsychiatric and developmental disorders (Haase et al, 2021; Kozlowska et al, 2021; Liu & McNally, 2021; Nie et al, 2021; Nomura et al, 2021) and neurodegenerative diseases (Brosseron et al, 2021; Butler et al, 2021; Chatterjee et al, 2021; Korecka & Shaw, 2021; Sathe et al, 2021; Trinh et al, 2021; Yuede et al, 2021). Similarly, studies into neuroinflammation and neuroimmunology are a growing area within the journal, such that in 2021 we published a special issue dedicated to this topic (https://onlinelibrary.wiley.com/toc/14714159/2021/158/1).…”
Section: Figurementioning
confidence: 99%